2014
DOI: 10.3389/fnsys.2014.00061
|View full text |Cite
|
Sign up to set email alerts
|

CA1 hippocampal network activity changes during sleep-dependent memory consolidation

Abstract: A period of sleep over the first few hours following single-trial contextual fear conditioning (CFC) is essential for hippocampally-mediated memory consolidation. Recent studies have uncovered intracellular mechanisms required for memory formation which are affected by post-conditioning sleep and sleep deprivation. However, almost nothing is known about the circuit-level activity changes during sleep that underlie activation of these intracellular pathways. Here we continuously recorded from the CA1 region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(142 citation statements)
references
References 40 publications
19
123
0
Order By: Relevance
“…This suggests that locking of neuronal firing with network oscillations, and associated stabilization of network functional connectivity patterns, is driven by synaptic potentiation between engram neurons and other neurons in the network. This agrees with previous experimental results, showing that contextual fear memory consolidation is associated with both increased theta-band oscillations, and increased FuNS, during sleep in the hours immediately following conditioning (17,18,20).…”
Section: Introduction Of Memory Traces Augments Network Oscillatory Dsupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests that locking of neuronal firing with network oscillations, and associated stabilization of network functional connectivity patterns, is driven by synaptic potentiation between engram neurons and other neurons in the network. This agrees with previous experimental results, showing that contextual fear memory consolidation is associated with both increased theta-band oscillations, and increased FuNS, during sleep in the hours immediately following conditioning (17,18,20).…”
Section: Introduction Of Memory Traces Augments Network Oscillatory Dsupporting
confidence: 93%
“…C57BL/6J mice implanted with bundles of CA1 stereotrodes either underwent CFC (placement into a novel environmental context, followed 2.5 min later by a 2-s, 0.75 mA foot shock; n = 5 mice), sham conditioning (placement in a novel context without foot shock; Sham; n = 3 mice), or CFC followed by 6 h of sleep deprivation (a manipulation known to disrupt fear memory consolidation [18,19,27]; SD; n = 5 mice) ( Figure 2 ). Spike data from individual neurons was discriminated offline using standard methods (consistent waveform shape and amplitude on the two stereotrode wires, relative cluster position of spike waveforms in principle component space, ISI ≥ 1 ms) (5,17,18,20,28). Only neurons that were stably recorded and reliably discriminated throughout the entire baseline and post-conditioning period were included in subsequent analyses of network dynamics.…”
Section: Hippocampal Network Stabilization In Vivo Predicts Effectivementioning
confidence: 99%
See 1 more Smart Citation
“…Tsujimoto et al [50,51] showed that theta oscillations were observed in the PFC, both in the local field potential and in the spiking of single neurons in a monkey self-initiated hand movement task. Ognjanovski [52] had reported that functional connectivity of spike timing relationships among recorded neurons within the CA1 network became more stable during consolidation of mice con-textual fear conditioning. Theta oscillations are also very important component of the interaction between the prefrontal cortex and the hippocampus and are also the carrier of functional networks linking the mPFC with the basolateral amygdala during contextual fear conditioning memory [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Theta oscillation has been suggested to support of a neural code [49], especially in PFC and in hippocampus. Ognjanovski [52] had reported that functional connectivity of spike timing relationships among recorded neurons within the CA1 network became more stable during consolidation of mice con-textual fear conditioning. Tsujimoto et al [50,51] showed that theta oscillations were observed in the PFC, both in the local field potential and in the spiking of single neurons in a monkey self-initiated hand movement task.…”
Section: Figurementioning
confidence: 99%